2018
DOI: 10.1093/cvr/cvy197
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress induces cardiac dysfunction through architectural modifications and alteration of mitochondrial function in cardiomyocytes

Abstract: Our findings show that ER stress induces cytoarchitectural and metabolic alterations in cardiomyocytes and provide evidences that ER stress could represent a primary mechanism that contributes to the impairment of energy metabolism reported in most cardiac diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…These data are also in agreement with the results obtained in animal models of T2DM (34). Interestingly, induction of ER stress by tunicamycin can also induce profound mitochondrial remodeling, including decreased ability to process fatty acids (16). Whether ER stress is the initiator, or works concomitantly with other disturbances (e.g., fatty acid overload of cardiomyocytes) leading to the downward spiral of adverse mitochondrial remodeling in human diabetic myocardium, remains to be investigated.…”
Section: Er Stress and Apoptosis In Diabetic Myocardiumsupporting
confidence: 88%
See 1 more Smart Citation
“…These data are also in agreement with the results obtained in animal models of T2DM (34). Interestingly, induction of ER stress by tunicamycin can also induce profound mitochondrial remodeling, including decreased ability to process fatty acids (16). Whether ER stress is the initiator, or works concomitantly with other disturbances (e.g., fatty acid overload of cardiomyocytes) leading to the downward spiral of adverse mitochondrial remodeling in human diabetic myocardium, remains to be investigated.…”
Section: Er Stress and Apoptosis In Diabetic Myocardiumsupporting
confidence: 88%
“…Quantitative RT-PCR of total ventricular RNA was performed as previously described (16). mRNA levels for all target genes (PPARa [peroxisome proliferator-activated receptor a], FAT/CD36 [fatty acid translocase/cluster of differentiation 36], and CPT1 [carnitine palmitoyltransferase 1]) were normalized to Ywhaz and PolR2A levels.…”
Section: Rna Isolation and Quantitative Rt-pcrmentioning
confidence: 99%
“…In addition, we found that inhibition of ER stress-induced autophagy by 3-MA or CQ triggers cell death, suggesting that activation of autophagy may counteract cell death and serve as a cardioprotective mechanism against ER stress. The impairment of the mitochondrial function associated with ER stress-induced heart injury ( [34] and Figure 5A) led us to investigate the involvement of mitophagy, a form of autophagy that selectively eliminates damaged mitochondria. By electron microscopy and subcellular fractionation, we demonstrated that autophagic vacuoles can contain damaged mitochondria and that Parkin is translocated to mitochondria under ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing body of studies has noted that the dysregulated endoplasmic reticulum (ER) stress is a critical positive factor deeply involved in cardiomyocyte apoptosis occurring in cardiovascular diseases including MI, 5‐8 rendering it as a potential therapeutic target in MI 9 . ER stress can induce cardiac dysfunction via architectural modifications and altering mitochondrial function in cardiomyocytes 10 . Lately, the NADPH oxidase, 11 calpain‐1 12 and sestrin2‐mTORC1 signalling 13 have been implicated in ER stress modulation in MI.…”
Section: Introductionmentioning
confidence: 99%
“…9 ER stress can induce cardiac dysfunction via architectural modifications and altering mitochondrial function in cardiomyocytes. 10 Lately, the NADPH oxidase, 11 calpain-1 12 and sestrin2-mTORC1 signalling 13 have been implicated in ER stress modulation in MI. However, how ER stress is regulated is not fully understood.…”
mentioning
confidence: 99%